Healing at implants installed concurrently to maxillary sinus floor elevation with Bio-Oss® or autologous bone grafts. A histo-morphometric study in rabbits - De Santis, Enzo; Lang, Niklaus P.; Ferreira, Sabrina [UNESP]; Rangel Garcia Jr, Idelmo [UNESP]; Caneva, Marco; Botticelli, Daniele [UNESP] (Wiley, 2017)
Objective: To compare the healing at elevated sinus floors augmented either with deproteinized bovine bone mineral (DBBM) or autologous bone grafts and followed by immediate implant installation. Material and methods: Twelve albino New Zealand rabbits were used. Incisions were performed along the midline of the nasal dorsum. The nasal bone was exposed. A circular bony widow with a diameter of 3 mm was prepared bilaterally, and the sinus mucosa was detached. Autologous bone (AB) grafts were collected from the tibia. Similar amounts of AB or DBBM granules were placed below the sinus mucosa. An implant with a moderately rough surface was installed into the elevated sinus bilaterally. The animals were sacrificed after 7 (n = 6) or 40 days (n = 6). Results: The dimensions of the elevated sinus space at the DBBM sites were maintained, while at the AB sites, a loss of 2/3 was observed between 7 and 40 days of healing. The implants showed similar degrees of osseointegration after 7 (7.1 ± 1.7%; 9.9 ± 4.5%) and 40 days (37.8 ± 15%; 36.0 ± 11.4%) at the DBBM and AB sites, respectively. Similar amounts of newly formed mineralized bone were found in the elevated space after 7 days at the DBBM (7.8 ± 6.6%) and AB (7.2 ± 6.0%) sites while, after 40 days, a higher percentage of bone was found at AB (56.7 ± 8.8%) compared to DBBM (40.3 ± 7.5%) sites. Conclusions: Both Bio-Oss® granules and autologous bone grafts contributed to the healing at implants installed immediately in elevated sinus sites in rabbits. Bio-Oss® maintained the dimensions, while autologous bone sites lost 2/3 of the volume between the two periods of observation.
Keywords: animal study; autologous bone graft; bone formation; bone healing; dental implants; deproteinized bovine bone mineral; histometry; lateral approach; morphometry; osseointegration; Schneiderian membrane; sinus floor elevation